Investigating paternal preconception risk factors for adverse pregnancy outcomes in a population of internet users. Issue 1 (December 2016) - Agricola, Eleonora; Gesualdo, Francesco; Carloni, Emanuela; D'Ambrosio, Angelo; Russo, Luisa; Campagna, Ilaria; Pandolfi, Elisabetta; Tozzi, Alberto
Abstract Background Paternal preconception risk factors such as smoking, exposure to environmental substances, medication use, overweight and advanced age correlate with the occurrence of malformations and birth defects in the offspring. Nonetheless, the prevalence of risk factors for adverse pregnancy outcomes in the male population has been scarcely investigated and no report on preconception interventions targeting prospective fathers is available. We conducted a web-based survey to measure the prevalence of paternal preconception risk factors for adverse pregnancy outcomes in an Italian population of Internet users. Methods Prospective or expectant fathers were enrolled during a four-week period through two of the main Italian web-sites dedicated to preconception, pregnancy, childhood and family care. Participants filled in a web questionnaire regarding preconception risk factors for adverse pregnancy outcomes. Logistic regression analysis was used to explore the predictors of paternal preconception risk factors. Results We enrolled 131 prospective and 205 expectant fathers. More than half of the total participants used medications during the preconception period, 35 % were smokers and 8 % were obese. Exposure to environmental substances was declared by almost 20 % of the participants, with the group including pesticides/herbicides/professional paints being the most prevalent. More than a half of the study sample included men aged over 35 years. According to the multivariate analysis, smoking and exposure to environmental toxics were less frequent among individuals with a university degree (respectively: OR = 0.52; 95 % CI 0.32–0.84; OR = 0.52; 95 % CI 0.29–0.93). Paternal obesity and medication use in the preconception period were not associated with any of the independent variables. Conclusions The prevalence of preconception risk factors among male population should not be neglected when planning preconception interventions, confirming that preconception health must be focused on the couple, rather than on women only.